2015
DOI: 10.2174/1574892810666150416111213
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-Proteasome Pathway an Emerging Anticancer Strategy for Therapeutics: A Patent Analysis

Abstract: The degradation of intracellular proteins is targeted by ubiquitin via non-lysosomal proteolytic pathway in the cell system. These ubiquitin molecules have been found to be conserved from yeast to humans. Ubiquitin proteasome machinery utilises ATP and other mechanisms for degrading proteins of cytosol as well as nucleus. This process of ubiquitination is regulated by activating the E3 enzyme ligase, involved in phosphorylation. In humans, proteins which regulate the cell cycle are controlled by ubiquitin; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Ubiquitin, a polypeptide containing 76 amino acid residues, is a key regulatory factor in the cell cycle and is widely expressed in eukaryotes[10-13]. In recent years, a growing number of ubiquitin-related low-molecular-weight proteins, known as ubiquitin-like proteins, have been identified and are associated with a variety of cell processes[14-16]. So far, two ubiquitin-like protein families, ubiquitin-like modifiers (UBLs) and ubiquitin-domain proteins, have been identified[17-19].…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin, a polypeptide containing 76 amino acid residues, is a key regulatory factor in the cell cycle and is widely expressed in eukaryotes[10-13]. In recent years, a growing number of ubiquitin-related low-molecular-weight proteins, known as ubiquitin-like proteins, have been identified and are associated with a variety of cell processes[14-16]. So far, two ubiquitin-like protein families, ubiquitin-like modifiers (UBLs) and ubiquitin-domain proteins, have been identified[17-19].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins are first ubiquitylated through 3 main steps: activation, conjugation and ligation, performed by ubiquitin-activating enzymes (E1s), ubiquitin-conjugating enzymes (E2s) and ubiquitin ligases (E3s), respectively; ubiquitylated proteins are then degraded by proteasomes. E3 ubiquitin ligases catalyze the final, but key step of the ubiquitination cascade through the specific recognition of the substrate target protein and E2 (1,2). It has been found that the RING-finger family is a major member of the E3 family.…”
Section: Introductionmentioning
confidence: 99%
“…The proteasomal degradation of some proteins can be promoted by phosphorylation [43]. To investigate the role of PIKKs in this phenomenon, HEK293 cells were pre-treated with wortmannin or LY294002 for 30 min and then treated with MMC for 6 h. Wortmannin is a broad inhibitor of PIKKs that irreversibly inhibits DNA-PK and ATM, whereas LY294002 is a potent inhibitor of class I phosphoinositide 3-kinases but does not efficiently inhibit PIKKs even at high concentrations [42, 44].…”
Section: Resultsmentioning
confidence: 99%